Satriana Didiek Isnanta MAKNA LORO BLONYO DAN DEFORESTASI DALAM PENCIPTAAN KARYA SENI INTERMEDIA - Satriana Didiek Isnanta; Much. Sofwan Zarkasi; Asmoro Nurhadi Panindias (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2020)
This research was designed as an experimental study of intermedia art creation based research by reinterpretingthe loro blonyo statue as a source of ideas for creating works. Loro Blonyo is a pair of wooden sculpturesconsisting of a female statue and accompanied by a man wearing a Javanese traditional wedding dress in asitting position. Broadly, the meaning of the Loro Blonyo statue for the Javanese people is the unity of thecouple as a reflection of the harmony of the Javanese mind and harmony. The meaning of the loro blonyostatue is then analyzed, elaborated and reinterpreted. This research is an artistic study with a focus on thestudy of the creation of intermedia art creation using various media based on conceptual thinking with aninterdisciplinary approach. The purpose of this creation is to create a multi-media installation art that usesvisual, motion and sound elements. This artistic research method uses Dharsono’s Creative Creation (2016):research with are ethic and emic approach, exploration, experimentation and formation approach. The resultsof the research were concluded and became the basis for the concept of space-based intermedia artwork,namely multi-media installation art with a visual form of local culture as a strengthening of national identity.